Effects of Monetary Incentives in Physician Groups: A Systematic Review of Reviews - Heider, Ann-Kathrin; Mang, Harald (Applied Health Economics and Health Policy, 2020)
Background Reimbursement systems that contribute to the cooperation and integration of providers have become increasingly important within the healthcare sector. Reimbursement systems not only serve as payment mechanisms but also provide control and incentive functions. Thus, the design of reimbursement systems is extremely important. Objectives The aims of this systematic review were to describe and gain a better understanding of the effects of monetary incentives in the setting of physician groups. Methods In January 2020, we searched the MEDLINE (PubMed), Cochrane Library, CINAHL, PsycINFO, EconLit, and ISI Web of Science databases as well as the gray literature and authors' personal collections. Results We included 21 reviews containing seven different incentive schemes/initiatives. The study settings and outcome measures varied considerably, as did the results within the incentive schemes and initiatives. However, we found positive effects on process quality for two types of incentives: pay-for-performance and accountable care organizations. The main limitations of this review were the variations in study settings and outcome measures of the studies included. Conclusions Monetary incentives in healthcare are often implemented as a control measure and are supposed to increase quality of care and reduce costs. The heterogeneity of the study results indicates that this is not always successful. The results reveal a need for research into the effects of monetary incentives in healthcare.
CRIS-Team WoS Importer:2020-04-10

Effects of Non-monetary Incentives in Physician Groups-A Systematic Review - Heider, Ann-Kathrin; Mang, Harald (American Journal of Health Behavior, 2023)
Objectives: Healthcare expenditures in western countries have been rising for many years. This leads many countries to develop and test new reimbursement systems. A systematic review about monetary incentives in group settings indicated that a sole focus on monetary aspects does not necessarily result in better care at lower costs. Hence, this systematic review aims to describe the effects of non- monetary incentives in physician groups. Methods: We searched the databases MEDLINE (PubMed), The Cochrane Library, CINAHL, PsycINFO, EconLit, and ISI Web of Science. Grey literature search, reference lists, and authors' personal collection provided additional sources. Results: Overall, we included 36 studies. We identified 4 categories of interventions related to non-monetary incentives. In particular, the category of decision support achieved promising results. However, design features vary among different decision support systems. To enable effective design, we provide an overview of the features applied by the studies included. Conclusions: Not every type of non-monetary incentive has a positive impact on quality of care in physician group settings. Thus, creating awareness among decision-makers regarding this matter and extending research on this topic can contribute to preventing implementation of ineffective incentives, and consequently, allocate resources towards tools that add value.
CRIS-Team Scopus Importer:2023-09-01

Integration of Risk Scores and Integration Capability in Electronic Patient Records - Heider, Ann-Kathrin; Mang, Harald (Applied Clinical Informatics, 2022)
BACKGROUND: Digital availability of patient data is continuously improving with the increasing implementation of electronic patient records in physician practices. The emergence of digital health data defines new fields of application for data analytics applications, which in turn offer extensive options of using data. Common areas of data analytics applications include decision support, administration, and fraud detection. Risk scores play an important role in compiling algorithms that underlay tools for decision support. OBJECTIVES: This study aims to identify the current state of risk score integration and integration capability in electronic patient records for cardiovascular disease and diabetes in German primary care practices. METHODS: We developed an evaluation framework to determine the current state of risk score integration and future integration options for four cardiovascular disease risk scores (arriba, Pooled Cohort Equations, QRISK3, and Systematic Coronary Risk Evaluation) and two diabetes risk scores (Finnish Diabetes Risk Score and German Diabetes Risk Score). We then used this framework to evaluate the integration of risk scores in common practice software solutions by examining the software and inquiring the respective software contact person. RESULTS: Our evaluation showed that the most widely integrated risk score is arriba, as recommended by German medical guidelines. Every software version in our sample provided either an interface to arriba or the option to implement one. Our assessment of integration capability revealed a more nuanced picture. Results on data availability were mixed. Each score contains at least one variable, which requires laboratory diagnostics. Our analysis of data standardization showed that only one score documented all variables in a standardized way. CONCLUSION: Our assessment revealed that the current state of risk score integration in physician practice software is rather low. Integration capability currently faces some obstacles. Future research should develop a comprehensive framework that considers the reasonable integration of risk scores into practice workflows, disease prevention programs, and the awareness of physicians and patients.
CRIS-Team Scopus Importer:2022-09-16

What do patients say about their physicians? an analysis of 3000 narrative comments posted on a German physician rating website. - Emmert, Martin; Meier, Florian; Heider, Ann-Kathrin; Dürr, Christoph; Sander, Uwe (Health policy (Amsterdam, Netherlands), 2014)
BACKGROUND Physician rating websites (PRWs) could be shown to have an impact on physician choice making. However, little research has been carried out to assess the content and nature of narrative comments. OBJECTIVE The aim of this study was to explore the concerns of patients who commented on physician care and to address and enhance patient satisfaction. METHODS Content analysis of 3000 randomly selected narrative comments from the German PRW, jameda, from 2012. We therefore developed a theoretical categorization framework addressing physician, staff, and practice related patient concerns. FINDINGS In total, 50 sub-categories addressing the physician (N=20), the office staff (N=13), and the practice (N=17) were derived from the content of all comments. The most frequently mentioned concerns were assessing the professional competence of the physician (63%, N=1874) and friendliness of the physician (38%, N=1148). Thereby, 80% of all comments (mean length 45.3 words ± 42.8) were classified as positive, 4% as neutral and 16% as negative. CONCLUSION Users of the German PRW, jameda, are mostly satisfied with their physicians. However, physicians should focus on the time spent with the patients, waiting time, as well as on taking the patients more seriously.